Building a Healthy Retail Community: Lessons from Little Giants in Kansas - Darling, David L. (My University, 1997)
This publication provides ideas on how to build a healthy and sustainable community of retailers in order to minimize leakage and increase retail capture.
MF2325_1998_04
Keywords: MF2325; Economics; MF